Innate immune response in Neospora caninum and BoAHV-1 coinfection: The interaction of TLRs and cathelicidins - Plá, Natalia (2024)
Neospora caninum causes significant global economic losses due to abortions in cattle. Immunosuppression induced by viral infection worsens neosporosis. However, the innate immune mechanisms in N. caninum and BoAHV-1 co-infections remain unknown. We previouslyshowed an overexpression of toll-like receptor (TLR) 7 and LL-37 human cathelicidin in this co-infection. This study investigated in vitro effects of bovine alpha-herpesvirus-1 (BoAHV-1) infection on TLRs and cathelicidin antimicrobial peptides signaling, and N. caninum replication in co-infected neuronal cells. Human neuroblastoma SH-SY5Y cells were pretreated with chloroquine (inhibitor of endosomal TLRs, 10 µg/ml), imiquimod (agonist of TLR7, 5 µg/ml),sodium butyrate (promoter of endogenous cathelicidin, 4 mM), or subjected to silencing of LL-37 (shLL-37), followed by infection with the reference strains N. caninum NC-1 (MOI: 0.2) and BoAHV-1 Cooper (MOI: 0.1). At 24 h post-infection, gene expression levels of key immune molecules involved in TLR mediated signaling pathways (NF-κβ, MyD88, IRF3, and IRF7) were assessed by RT-qPCR and tachyzoite replication was examined microscopically. The results indicated that N. caninum replication in coinfection with BoAHV-1 was significantly decreased both intracellularly and extracellularly after chloroquine pretreatment and shLL-37 compared to imiquimod and sodium butyrate treatments. This reduction was accompanied in co-infection by a significant increase, with respect to the control, in MyD88 and IRF3 expression (3.9-fold and 5.5- fold, respectively, p<0.05) after chloroquine treatment, and a decrease in IRF3 expression after shLL-37 (0.409-fold, p<0.05). While treatments with imiquimod and sodium butyrate resulted in a significant decrease, with respect to the control, in the expression of three of the four molecules analyzed (NF-κβ: 0.126 and 0.074; MyD88: 0.365 and 0.508; IRF7: 0.078 and 0.01, respectively, p<0.05). These findings highlight the role of TLR7 and LL-37 in co-infection, emphasizing their impact on dynamics. TLR7 and LL-37 regulate BoAHV- 1 replication, promoting N. caninum replication when both pathogens are present.